Lymphomatoid Papulosis Type E With T-Cell Receptor Gamma Positivity - Namasondhi A; Rutnin S; Jerasutus S; Boonsakan P; Triyangkulsri K (Clinical, Cosmetic and Investigational Dermatology)
Amornrut Namasondhi,1 Suthinee Rutnin,1 Suthep Jerasutus,1 Paisarn Boonsakan,2 Korn Triyangkulsri1 1Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 2Department of Pathology, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Korn Triyangkulsri, Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, 270 Rama VI Road, Ratchathewi, Bangkok, 10400, Thailand, Tel +66-2-2011141, Fax +66-2-201-1211, Email korn.triy@gmail.comAbstract: Lymphomatoid papulosis (LyP) is currently categorized as a primary lymphoproliferative disorder that follows a chronic, recurrent clinical course. The diagnosis of LyP is mainly based on clinical presentation and histopathological correlation. Six subtypes of LyP have been described and recognized, each with different histological features and sometimes distinct clinical presentations. LyP type E is a subtype that histologically shows angioinvasion and angiodestruction by CD8 and CD30-positive pleomorphic T cells. Clinically, it usually presents with a few large necrotic nodules or ulcers on the trunk or extremities, unlike other subtypes of LyP. Despite an indolent clinical course, long-term follow-up is necessary due to the risk of developing concurrent or secondary lymphoma. In this report, we demonstrate a case of lymphomatoid papulosis type E presented with widespread small papulonecrotic eruptions, an atypical clinical manifestation, and an unusual immunohistochemical profile. The biopsy revealed CD8, CD30, CD56, and TCR-γ-positive atypical lymphocytic infiltration with angioinvasion and angiodestruction. The patient was successfully treated with low-dose methotrexate.Keywords: CD30, CD56, cutaneous T-cell lymphoma, lymphoproliferative disorder, papulonecrotic skin disease